Synthesis and in vitro evaluation of hydrazinyl phthalazines against malaria parasite, Plasmodium falciparum. Issue 14 (15th July 2016) - Subramanian, Gowtham; Babu Rajeev, C.P.; Mohan, Chakrabhavi Dhananjaya; Sinha, Ameya; Chu, Trang T.T.; Anusha, Sebastian; Ximei, Huang; Fuchs, Julian E.; Bender, Andreas; Rangappa, Kanchugarakoppal S.; Chandramohanadas, Rajesh; Basappa,
Graphical abstract: Abstract: In this report, we describe the synthesis of 1-(Phthalazin-4-yl)-hydrazine using bronsted acidic ionic liquids and demonstrate their ability to inhibit asexual stage development of human malaria parasite, Plasmodium falciparum . Through computational studies, we short-listed chemical scaffolds with potential binding affinity to an essential parasite protein, dihydroorotate dehydrogenase (DHODH). Further, these compounds were synthesized in the lab and tested against P. falciparum . Several compounds from our library showed inhibitory activity at low micro-molar concentrations with minimal cytotoxic effects. These results indicate the potential of hydralazine derivatives as reference scaffolds to develop novel antimalarials.